2021
DOI: 10.1007/s10140-021-01931-4
|View full text |Cite
|
Sign up to set email alerts
|

You’ll see it when you know it: granulomatous mastitis

Abstract: Granulomatous mastitis (GM) is an under-recognized and under-diagnosed disease. Patients with GM often present to the emergency room with a painful breast mass, nipple retraction, and skin changes. This pictorial essay will review the clinical presentation and imaging appearance of GM, BI-RADS reporting parameters, differential diagnoses, and diagnostic challenges posed by this disease. Early and accurate diagnosis is essential, as misdiagnosis can result in repeated core biopsies, leading to fistulae and sinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Occasionally, a typical granuloma may be absent, and only a histiocytic infiltrate is present. Common staining methods such as PAS, Grocott, and Ziehl yield negative results [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, a typical granuloma may be absent, and only a histiocytic infiltrate is present. Common staining methods such as PAS, Grocott, and Ziehl yield negative results [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies showed the long-lasting condition of NPM and the potential repeated breast surgeries could negatively affect the physical and mental health of patients with higher medical costs [24] , few studies have provided a comprehensive description of severe NPM episodes. Most of the previous studies are case reports and are limited in sample size, data quality, valid study design, and analysis [3] , and only described the characteristics of NPM [25,26] . Few studies further investigated the risk factors associated with NPM severity.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies showed the long-lasting condition of NPM and the potential repeated breast surgeries could negatively affect the physical and mental health of patients with higher medical costs [24] , few studies have provided a comprehensive description of severe NPM episodes. Most of the previous studies are case reports and are limited in sample size, data quality, valid study design, and analysis [3] , and only described the characteristics of NPM [25,26] . Some evidence illustrated that increasing prolactin (PRL) level is highly related to NPM reoccurrence [27,28] , but few studies focused on the association between PRL level and NPM severity of rst time onset, or further investigated risk factors among NPM patients who need surgical treatment.…”
mentioning
confidence: 99%